An Alternative Prosthodontic Management of Maxillary Dentoalveolar Defect in a Patient With Cleft Palate and Lip: Case Report. (October 2019) - Szmidt, Monika; Górski, Maciej; Bendyk-Szeffer, Maja; Stogiera, Anna; Buczkowska-Radlińska, Jadwiga
Cleft palate/lip is a frequently occurring congenital anomaly; one in every 800 births results in such a problem. Different treatment options are available for replacing missing soft and hard tissues, including removable dental prostheses, fixed dental prostheses (FDPs), and implant prostheses. In the literature, according to different authors, there are different option standard for prosthetic treatment of cleft palate/lip. Some authors report that removable prosthesis is the choice in such cases, some of them regard conventional tooth-supported FDPs as a standard of care. In this case report, the prosthetic treatment of congenital cleft palate/lip was described. Upon the choice of the patient and patient's agreement, the direct construction Fibre-reinforced composite (FRC) adhesive bridge with pink composite gingival epithesis was performed.